Significance of the cranial neural crest. - Graham, A; Begbie, J; McGonnell, I (2004)
The cranial neural crest has long been viewed as being of particular significance. First, it has been held that the cranial neural crest has a morphogenetic role, acting to coordinate the development of the pharyngeal arches. By contrast, the trunk crest seems to play a more subservient role in terms of embryonic patterning. Second, the cranial crest not only generates neurons, glia, and melanocytes, but additionally forms skeletal derivatives (bones, cartilage, and teeth, as well as smooth muscle and connective tissue), and this potential was thought to be a unique feature of the cranial crest. Recently, however, several studies have suggested that the cranial neural crest may not be so influential in terms of patterning, nor so exceptional in the derivatives that it makes. It is now becoming clear that the morphogenesis of the pharyngeal arches is largely driven by the pharyngeal endoderm. Furthermore, it is now apparent that trunk neural crest cells have skeletal potential. However, it has now been demonstrated that a key role for the cranial neural crest streams is to organise the innervation of the hindbrain by the cranial sensory ganglia. Thus, in the past few years, our views of the significance of the cranial neural crest for head development have been altered. Developmental Dynamics 229:5-13, 2004.